Thomson backscattering from laser-generated, relativistically moving high-density electron layers - A Paz; S Kuschel; C Rödel; M Schnell; O Jäckel; M C Kaluza; G G Paulus (New Journal of Physics, 2012)
We show experimentally that extreme ultraviolet radiation is produced when a laser pulse is Thomson backscattered from sheets of relativistic electrons that are formed at the rear surface of a foil irradiated on its front side with a high-intensity laser. An all-optical setup is realized using the Jena titanium:sapphire ten-terawatt laser system with an enhanced amplified spontaneous emission background of 10 ^−12 . The main pulse is split into two: one of them accelerates electrons from thin aluminium foil targets to energies of the order of some MeV and the other, counterpropagating probe pulse Thomson-backscatters off these electrons when they exit the target rear side. The process produced photons within a wide spectral range of some tens of eV as a result of the broad electron energy distribution. The highest scattering intensity is observed when the probe pulse arrives at the target rear surface 100 fs after irradiation of the target front side by the pump pulse, corresponding to the maximum flux of hot electrons at the interaction region. These results can provide time-resolved information about the evolution of the rear-surface electron sheath and hence about the dynamics of the electric fields responsible for the acceleration of ions from the rear surface of thin, laser-irradiated foils.